Illegal Immigration, Border Enforcement, and Relative Wages: Evidence from Apprehensions at the U.S.-Mexico Border - Hanson, Gordon H; Spilimbergo, Antonio (American Economic Review, 1999)
Illegal Immigration, Border Enforcement, and Relative Wages: Evidence from Apprehensions at the U.S.-Mexico Border by Gordon H. Hanson and Antonio Spilimbergo. Published in volume 89, issue 5, pages 1337-1357 of American Economic Review, December 1999